A comunidade quilombola Abacatal e os aterros sanitários da região metropolitana de Belém: análise sobre a utilização do protocolo de consulta prévia, livre, informada e de boa-fé e os possíveis impactos ambientais das atividades dos aterros face à comunidade quilombola Abacatal/Aurá, Pará - ROSSO, Carolina Maria de Jesus (Universidade Federal do Pará, 2023)
The present research analyzes the utilization of the Protocol of Prior Assessments and in good faith for the Quilombola Abacatal/Aurá Community - Prior, Free, Informed and Good Faith Consultation Protocol for the Abacatal/Aurá Quilombola Community in the processes of administrative licensing the landfills of the metropolitan region of Belém (RMB): Aurá Sanitary Landfill Aurá Garbage Dump and Marituba’s Sanitary Landfill. In this sense, this analysis looked to contextualize the problems experienced by the Acabatal community, its titling, the rectification and additions processes, verifying the judicial demands required by the community, in which are demanded reparations, compensation or indemnity for environmental damages, or the annulment of the landfill licensing processes in lieu of the absence of the Protocol of Prior Assessments and in good faith for the Quilombola Abacatal/Aurá Community - Prior, Free, Informed and Good Faith Consultation Protocol for the Abacatal/Aurá Quilombola Community. The justifications for the present research project relates to the problematics experienced by the Abacatal community, result of social and political neglect, the judicial aggrandizement regarding this issue, in light of the debate around the necessity of observance to the Convenção OIT-169 and to the right to an ecologically balanced environment, as well as, personal growth, since it is a familiar theme, with focus on the professional area, referring to the urban public policies, thus rectifying its social, judicial and personal relevance, respectively. The research used the descriptive method of research, through the qualitative research technique in which the documentary analysis of the judicial and administrative environmental processes related to the Quilombola community of Abacatal, as well as the private enterprises that have participated in the installation and operation of the landfills. sanitary facilities, as well as bibliographical research with the survey of texts and academic works on the subject.